Comparison of the Sensitivity Test of Generic and Branded Antifungal Drugs Against Malassezia - Muh. Rikho Pratama H.S.; Andi Sitti Fahirah Arsal; Andi Masdipa; Wisudawan; Andi Alamanda Irwan (UNUSA Press, 2026)
Introduction: Malassezia furfur is a lipophilic yeast commonly associated with pityriasis versicolor, characterized by skin discoloration and mild pruritus. Antifungal therapy is available as generic and branded products, yet differences in laboratory efficacy and cost implications remain relevant for clinical decision-making. Objective: To compare the in vitro antifungal susceptibility of generic versus branded antifungal agents against M. furfur using the disk diffusion method and to consider the economic implications. Methods: A laboratory experimental study was conducted using disk diffusion susceptibility testing on M. furfur isolates. Generic ketoconazole was compared with several branded formulations. The primary outcome was the inhibition zone diameter as an indicator of antifungal effectiveness. Statistical analysis was performed using ANOVA followed by Tukey’s post hoc test to identify intergroup differences. Results: Both generic ketoconazole and branded antifungal agents demonstrated good inhibitory activity against M. furfur. Certain branded products, particularly Brand D showed a slightly larger mean inhibition zone diameter than the generic formulation. ANOVA and Tukey’s tests indicated statistically significant differences among some treatment groups. However, the incremental advantage observed in selected branded products was not proportional to their higher prices, as the generic drug remained substantially more affordable while maintaining comparable inhibitory performance. Conclusions: Based on the results, it is concluded that both generic and branded antifungal topical (ointment) and antifungal oral (capsule) demonstrated